AKAP13 Rho-GEF and PKD-Binding Domain Deficient Mice Develop Normally but Have an Abnormal Response to β-Adrenergic-Induced Cardiac Hypertrophy - Spindler, Matthew J. (Public Library of Science, 2013)
BACKGROUND: A-kinase anchoring proteins (AKAPs) are scaffolding molecules that coordinate and integrate G-protein signaling events to regulate development, physiology, and disease. One family member, AKAP13, encodes for multiple protein isoforms that contain binding sites for protein kinase A (PKA) and D (PKD) and an active Rho-guanine nucleotide exchange factor (Rho-GEF) domain. In mice, AKAP13 is required for development as null embryos die by embryonic day 10.5 with cardiovascular phenotypes. Additionally, the AKAP13 Rho-GEF and PKD-binding domains mediate cardiomyocyte hypertrophy in cell culture. However, the requirements for the Rho-GEF and PKD-binding domains during development and cardiac hypertrophy are unknown. METHODOLOGY/PRINCIPAL FINDINGS: To determine if these AKAP13 protein domains are required for development, we used gene-trap events to create mutant mice that lacked the Rho-GEF and/or the protein kinase D-binding domains. Surprisingly, heterozygous matings produced mutant mice at Mendelian ratios that had normal viability and fertility. The adult mutant mice also had normal cardiac structure and electrocardiograms. To determine the role of these domains during β-adrenergic-induced cardiac hypertrophy, we stressed the mice with isoproterenol. We found that heart size was increased similarly in mice lacking the Rho-GEF and PKD-binding domains and wild-type controls. However, the mutant hearts had abnormal cardiac contractility as measured by fractional shortening and ejection fraction. CONCLUSIONS: These results indicate that the Rho-GEF and PKD-binding domains of AKAP13 are not required for mouse development, normal cardiac architecture, or β-adrenergic-induced cardiac hypertrophic remodeling. However, these domains regulate aspects of β-adrenergic-induced cardiac hypertrophy.